Mitochondrial Function in Enamel Development - Costiniti, Veronica; Bomfim, Guilherme H.; Li, Yi; Mitaishvili, Erna; Ye, Zhi-wei; Zhang, Jie; Townsend, Danyelle M.; Giacomello, Marta; Lacruz, Rodrigo S. (Frontiers in Physiology, 2020)
Enamel is the most calcified tissue in vertebrates. Enamel formation and mineralization is a two-step process that is mediated by ameloblast cells during their secretory and maturation stages. In these two stages, ameloblasts are characterized by different morphology and function, which is fundamental for proper mineral growth in the extracellular space. Ultrastructural studies have shown that the mitochondria in these cells localize to different subcellular regions in both stages. However, limited knowledge is available on the role/s of mitochondria in enamel formation. To address this issue, we analyzed mitochondrial biogenesis and respiration, as well as the redox status of rat primary enamel cells isolated from the secretory and maturation stages. We show that maturation stage cells have an increased expression of PGC1α, a marker of mitochondrial biogenesis, and of components of the electron transport chain. Oxygen consumption rate (OCR), a proxy for mitochondrial function, showed a significant increase in oxidative phosphorylation during the maturation stage, promoting ATP production. The GSH/GSSG ratio was lower in the maturation stage, indicative of increased oxidation. Because higher oxidative phosphorylation can lead to higher ROS production, we tested if ROS affected the expression of AmelX and Enam genes that are essential for enamel formation. The ameloblast cell line LS8 treated with H2O2 to promote ROS elicited significant expression changes in AmelX and Enam. Our data highlight important metabolic and physiological differences across the two enamel stages, with higher ATP levels in the maturation stage indicative of a higher energy demand. Besides these metabolic shifts, it is likely that the enhanced ETC function results in ROS-mediated transcriptional changes.